A Case Study of Web-Based Communication for Online Teaching and Learning at a Christian University in Buddhist Thailand - Benya Lertsuwan; Rey Ty; Wutthichula Khunpatwattana; Benjamaporn Mekara (Religion and Social Communication)
Quality education, which is the fourth element of the sustainable development goals of the United Nations, suffered dramatically in the time of the pandemic. Unprepared, most academic institutions started to embark on web-based education. This research addressed the most and least effective learning experiences for both students and instructors in online learning and teaching. This case study employed both descriptive statistical data and qualitative information to have a well-rounded understanding of the phenomenon of digital education. This study used non-random, purposive, convenience, snowball, and quota sampling methods to invite research collaborators. Thematic analysis was employed to obtain rich qualitative insights that supplement the quantitative data. The raw data was collected from both instructors and students who were engaged in online education during the pandemic. The findings revealed that both instructors and students complained that the least effective learning experiences is the poor internet connectivity, as it is an obstacle that interrupted smooth flowing online learning and teaching. By presenting real-world insights, stressing significant findings, and offering recommendations, this article contributes to a more profound comprehension of web-based classroom. In this period of re-globalization after the end of the pandemic, online education is now mainstream.